PENGARUH KOMPETENSI PERANGKAT DESA TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA DI KOTA PAYAKUMBUH - Reski Ramadhani; Novera Martilova (BORJUIS: JURNAL OF ECONOMY, 2025)
This research aims to determine whether there is a significant influence between the competence of village officials on the accountability of village fund management. The population in this study is one of the village officials in Payakumbuh City, totaling 47 sub-districts. The sample in this study also consisted of 47 village officials using a satured sampling technique. The data collection method is a questionnaire. The data analysis method uses descriptive statistical analysis. The research result show that the competence of village fund management. This statement is based on the result of the partial test (t test) with a significance value of 0.008 which is 0.05 and seen from the calculated t value of 2.749 ˃ t table 2.011.